Relationship between depression and cardiovascular disease (review of literature) - E. V. Vinokurov (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
The article deals with the important issue in the field of consultative psychiatry - comorbid depressive disorders in patients with cardiovascular diseases. Depression is highly prevalent in cardiac patients. Patients with coronary artery disease, heart failure, atrial fibrillation and those undergoing implantable cardioverter-defibrillator placement are at increased risk for elevated depressive symptoms and for major depressive disorder. In patients with heart diseases, depression is chronic, persistent, and associated with worse health-related quality of life, recurrent cardiac events, and mortality. At present, pharmacologic and psychotherapeutic interventions appear to be safe and effective at reducing depressive symptoms in patients with cardiovascular diseases and may impact cardiac outcomes. Despite this, depression remains under-recognized and undertreated in patients at risk for or living with cardiovascular diseases. In this review, we summarize the evidence linking depression to increased risk of cardiovascular diseases and worse patient outcomes. The paper presents a review of the literature on the physiologic mechanisms implicated in the connection between depression and cardiovascular diseases. Impaired adherence to health behaviors and adverse physiological effects of depression, including inflammation, endothelial dysfunction, platelet hyperactivity, and autonomic nervous system abnormalities, may link depression with adverse cardiac outcomes. Future studies in this direction with involvement of cardiologists and psychiatrists should be held.